Planejamento popular de organização territorial da Comunidade Quilombola Barra da Aroeira – projetando o espaço de morar - Gomes, Andressa Caroline Silva Leitão (Universidade Federal do Tocantins, 2021)
This work presents the experience of popular participation in the organization of the territory of the Quilombo community Barra da Aroeira - located in the state of Tocantins - in the period 2017 - 2019, carried out through an extension action promoted by Projeto Raios de Sol, and progresses to the preliminary project of territorial organization of the community, with disposition of guidelines and spatialization of proposals built from popular education. The systematization of the extension experience brought here is a way to contribute in the academic field with the expansion of references of territorial ordering in traditional communities having the principle of popular participation, while advancing to the pre-project phase is intended to give back in a practical way and the plans developed with the population are applicable in order to contribute to the demarcation of the territory – constantly threatened by the agribusiness belt that is intensifying in its surroundings – and to help in the sustainable use of resources. For this purpose, participatory workshops were carried out with the community, searches in the Raios de Sol project archives, visits, and research in related bibliographies. It is noteworthy that the proposal phase is worked in a participatory and horizontal perspective, with a view to economic and social emancipation, in addition to appropriation and preservation of the territory, understanding the community as the protagonist in decisions about their living space.